On inequalities of Hermite-Hadamard type for co-ordinated \((α_1,m_1)\)-\((α_2,m_2)\)-convex functions - Bai, Shu-Ping; Sun, Jian; Qi, Feng (Global Journal of Mathematical Analysis, 2015)
In the paper, the authors establish some Hermite-Hadamard type integral inequalities for co-ordinated \((α_1,m_1)\)-\((α_2,m_2)\)-convex functions on a rectangle of the plane \(R_0^2\).